Unidirectional oblique propagation of exciton-polaritons in hybrid photonic crystals. (12th May 2017) - D'Andrea, A.; Tomassini, N.
Abstract: In this work we study theoretically the axial spectral asymmetry of a 1D hybrid (isotropic and anisotropic) photonic crystal for photon energies close to the electronic energy gaps of semiconductors (excitons). The non-normal optical properties of these resonant non-magnetic photonic crystals will be computed in the framework of exciton-polariton, by self-consistent solutions of the Maxwell-Schrödinger equations in the effective mass approximation. The tailoring of the hybrid photonic crystals, performed by implementing a simple two-layer "minimum model", and novel optical properties, due to the unidirectional polariton propagation, will be discussed.